1999
DOI: 10.1143/jjap.38.l1035
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Radiation from (111) InAs Surface Using 1.55 µm Femtosecond Laser Pulses

Abstract: We report the first observation of terahertz (THz) radiation from an undoped (111) InAs surface excited by 1.55 µm femtosecond laser pulses. The surface illuminated by an unfocused beam at an incidence angle of 45 degrees measured with respect to the surface normal emits THz radiation with weak dependence of the amplitude on the azimuthal angle. The results indicate that the radiation excited by the unfocused beam at a power density less than ∼1 W/cm2 is mainly explained by the surge current effect acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The radiation originates mainly from the surge current effect and the optical rectification effect can be neglected for the power density level adopted in this experiment. 4 In this case, the surge current direction is perpendicular to the sample surface without magnetic fields, resulting in horizontal polarization for THz radiation. 11 With application of the magnetic field, the vertical polarization component appears and strong enhancement of the overall spectral intensity is observed for both the horizontal and perpendicular components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiation originates mainly from the surge current effect and the optical rectification effect can be neglected for the power density level adopted in this experiment. 4 In this case, the surge current direction is perpendicular to the sample surface without magnetic fields, resulting in horizontal polarization for THz radiation. 11 With application of the magnetic field, the vertical polarization component appears and strong enhancement of the overall spectral intensity is observed for both the horizontal and perpendicular components.…”
Section: Resultsmentioning
confidence: 99%
“…2 Generally, both effects coexist in THz radiation from semiconductor surfaces. 3,4 Later the change of wave form and the increase in the amplitude of THz radiation were found for GaAs by applying external magnetic fields by Zhang et al 5 Sarukura et al have shown that InAs is a stronger THz emitter than GaAs and that the emission intensity increases monotonically with the external magnetic field intensity at least up to 1.7 T. 6 The enhancement of the radiation intensity under magnetic fields was confirmed for various semiconductors and the strongest radiation intensity was observed for InAs. 7 These results seem to hold promise for InAs as a compact strong THz emitter for THz spectroscopy and imaging without microfablication.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of investigations focused on the mechanism of THz emission from InAs. It was found that this material efficiently radiated THz pulses also when photo-excited with 1.550 µm laser [144].…”
Section: Inas and Other Narrow-gap Semiconductorsmentioning
confidence: 99%
“…148 LTEM has been also used for inspection of semiconductor devices. [149][150][151] Sakai et al 152 have demonstrated laser-induced THz emission from the surface of GaN, which can be used for determination of the defect density and surface potential.…”
Section: Laser-induced Thz Emission Spectroscopy For Visualization Ofmentioning
confidence: 99%